Optimization approach for bioethanol production from agro-industrial waste - Pascual Eduardo Murillo-Alvarado; Ernesto Flores Russell (Frontiers in Energy Research, 2022)
Seeking energy alternatives that are friendly to the environment without compromising the growth of society is becoming more widespread. Biofuels from biomass processing are a promising path toward the development of a biomass industry and the early replacement of fossil fuels. The purpose of this work is to determine the feasibility of generating biofuels through the use of agro-industrial waste through a mathematical model for the optimization of the supply chain for the production of biofuels from waste generated by the food processors in the municipality of Zamora, Michoacán, Mexico. This case study considers the available raw material, waste from the food industries, the period of time in which these are available, as well as the possible places for processing and obtaining biofuels. The results establish that it is possible to obtain 7.27 × 107 l/year of bioethanol through the processing of 3.27 × 106 tons/year of organic waste, which generates a profit of 4.37 × 107 USD/year.